Fixed Up. - Jane, Maddie (Harlequin Enterprises, Australia Pty Ltd, 2016)
A fresh new voice in contemporary romance, Maddie Jane debuts her romantic comedy novel about a woman who knows how to fix things and the man who wants to convince her that DIY is more fun with two... Toppling from her very high heels into Luke Colton's arms is not the impression Harper Cassidy likes to make. She is strong, independent, and on a personal mission to teach DIY skills to women, and he is all wrong - determined to get involved, determined to help her, and determined to mess with her self-control and self-imposed single lifestyle. Harper has been more than clear that her plans don't include him, but there's something about a woman that knows her way around a power tool that has Luke too enthralled to walk away. Taking his mother along to Harper's DIY for women classes is the perfect excuse to watch her in action, and maybe convince her that doing it for yourself doesn't always mean having to go it alone.
Imprint: Escape Publishing.
Keywords: Fiction - Romance - Contemporary; Australian